Brain Region- and Age-Dependent 5-Hydroxymethylcytosine Activity in the Non-Human Primate - Xu, Yanru; Zhong, Liying; Wei, Huixian; Li, Yuwei; Xie, Jiaxiang; Xie, Leijie; Chen, Xiusheng; Guo, Xiangyu; Yin, Peng; Li, Shihua; Zeng, Junwei; Li, Xiao-Jiang; et al. (Frontiers in Aging Neuroscience, 2022)
Because of difficulty in collecting fresh brains of humans at different ages, it remains unknown how the epigenetic regulation occurs in the primate brains during aging. In the present study, we examined genomic distribution of 5hmC, an indicator of DNA methylation, in the brain regions of non-human primates (rhesus monkeys) at ages of 2 (juvenile), 8 (young adult), and 17 (old) years. We found that genomic 5hmC distribution was accumulated in the monkey brain as age increases and displayed unique patterns in the cerebellum and striatum in an age-dependent manner. We also observed a correlation between differentially hydroxymethylated regions (DhMRs) and genes that contribute to brain region-related functions and diseases. Our studies revealed for the first time the brain-region and age-dependent 5hmC modifications in the non-human primate and the association of these 5hmC modifications with brain region-specific function and potentially aging-related brain diseases.